The Study of Electrical Properties and Photocurrent of Polyaniline/ fluorescein films - Hameed A. Hamadi (University of Thi-Qar Journal of Science, 2019)
Electrical conductivity and visible photo current (PC) measurements have been performed on thick film (10 μm) of polyaniline modified with (1x10-4)fluorescein organic dye were all measurements have been made using Sandwich structureof aluminum and semitransparent aluminum with area (0.03 cm2) circular electrode. TheD.C. conductivity was measured as a function of doping ratio with iodine using thetechnique of two probes.All current measurements have been made at steady stateconditions were the obtained results showed that the domain conduction mechanisms wasidentified as space charge limited current (SCLC) and the D.C. bulk conductivity of pure films was 6.6x10-9S.cm-172mole) content of ,and this conductivity is increased by 5.4 times of films with doping ratio equal to 2% . Photocurrent (PC) was measured with specified wave length as a function of applied voltage were the intensity of the incident light was 295 lux/mfor each case. The obtained results of PC showed that the observed photons form excites, andthe caste films have poor photoconductivity while maximum peak of D.C. conductivityunder illumination was obtained near Yellow region of visible light were the absorption ofincident light is high and free carriers are available. Also the obtained results showed that the cut-off wave length is near red region, and the recombination process is bulk finally Another noticeable remark, that the photocurrent isincreased by amount of 800 times & D.C conductivity is increased by 1300 comapred tomagnitude at darkness.